PEMANFAATAN SOLID KELAPA SAWIT DAN SP-36 UNTUK MENINGKATKAN PERTUMBUHAN DAN HASIL CABAI RAWIT (Capsicum frutescens L.) PADA SPODOSOLS: Utilization of Soil Palm Oil and SP-36 to Increase Growth and Yield of Cayenne pepper (Capsicum frutescens L.) on Spodosols - Asie, Erina Riak; Prasetya, Prasetya (AgriPeat, 2023)
This study was conducted to examine the utilization of solid waste oil palm and SP-36 on the growth and yield of cayenne pepper on spodosols. This experiment used a factorial Completely Randomized Design (CRD) consisting of 2 treatment factors and 3 replication. The first factor is the provision of solid palm oil consisting of 4 (four) levels, namely without the provision of solid palm oil, 10 ton.ha-1, 20 ton ha-1, and 30 ton ha-1 solid palm oil. The second factor is the administration of SP-36 consisting of 4 (four) levels, namely : without giving SP-36, 100 kg ha-1, 200 kg ha-1 and 300 kg ha-1 SP-36. The variables observed were plant height, number of flowers plant-1, shoot/root ratio, dry weight plant-1, and fresh weight of fruit plant-1. The results showed that there was an interaction effect between oil palm solids and SP-36 on plant height, number of flowers, and fresh fruit weight of plant-1 on spodosol soil. The combination of solid oil palm 20 tons ha-1 and SP-36 200 kg ha-1 was the best combination in increasing the growth and yield of cayenne pepper on spodosols and produced the heaviest fresh fruit weight plant-1, which was 68,33 g plant-1.